Controllable Superlubricity System of Polyalkylene Glycol Aqueous Solutions under Various Applied Conditions. Issue 7 (21st June 2020) - Liu, Wenrui; Wang, Hongdong; Liu, Yuhong; Zhang, Caixia; Luo, Jianbin
Abstract: It has been recently demonstrated that the superlubricity behavior of polyalkylene glycol (PAG) aqueous solutions can be achieved in a wide variety of applied conditions. However, certain parameters are expected to be adjusted further to achieve a more controllable superlubricity system. Herein, it is demonstrated that an ultralow friction coefficient can be obtained by concentrated PAG aqueous solutions (80 wt% HB‐260) as the contact pressure becomes relatively low (37 MPa). Meanwhile, the superlubricity state can be adjusted in a timely manner by adjusting the relative sliding speed. Here, the viscosity of the PAG aqueous solution (determined by its concentration and molecular weight) and applied conditions, including contact pressure and relative sliding speed, are considered as critical parameters influencing the lubricating performance. According to the theoretical analysis, the superlubricity state is confirmed and a fitted superlubricity region is proposed, which provides a comprehensive guide for achieving controllable superlubricity in the future. Abstract : Polyalkylene glycol (PAG) aqueous solutions are newfound water‐based lubricants that exhibit super‐low friction coefficients. By adjusting certain parameters, such as the viscosity, the applied pressure, and the sliding speed, controllable superlubricity of these solutions is able to be achieved. Then, a fitting superlubricity region is proposed to aid the selection of polymer lubricants to be used in various industries.